2014
DOI: 10.1038/nrcardio.2014.22
|View full text |Cite|
|
Sign up to set email alerts
|

Oral anticoagulants for Asian patients with atrial fibrillation

Abstract: Anticoagulation is the most-important intervention to prevent stroke in patients with atrial fibrillation (AF). Despite a lower point prevalence of AF in Asian communities and Asian countries than in other populations, individuals of Asian ethnicity are at a disproportionately high risk of stroke and have greater consequent mortality. Warfarin and other vitamin K antagonists are conventionally used for anticoagulation, and demonstrably reduce the risk of stroke and all-cause mortality in patients with AF. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 143 publications
4
34
0
Order By: Relevance
“…However, there is insufficient evidence to support the clinical utility of genetic testing prior to warfarin initiation [58]. Non-vitamin K antagonists have been proposed as a potentially safer option for anticoagulation in Asians [59], but more research is needed to determine the risks and benefits of these newer medications. 2.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is insufficient evidence to support the clinical utility of genetic testing prior to warfarin initiation [58]. Non-vitamin K antagonists have been proposed as a potentially safer option for anticoagulation in Asians [59], but more research is needed to determine the risks and benefits of these newer medications. 2.…”
Section: Discussionmentioning
confidence: 99%
“…1 Moreover, antiplatelet agents have been commonly used (56%) for stroke prevention among Chinese patients with AF, 18 but this approach using antiplatelet agents is neither safe nor effective for stroke prevention in patients with AF. 19 Data on OAC use in developed countries are available from many previous studies. For example, the US nationwide ORBIT-AF study showed that 76% of AF outpatients received OAC (71% warfarin and 5% dabigatran), and the use of OAC was even higher (80%) among those with CHADS₂ scores ≥ 2.…”
Section: Discussionmentioning
confidence: 99%
“…Asian patients are more sensitive to the anticoagulant effects of warfarin and have higher rates of bleeding when they are in the therapeutic range (12). Therefore, frequent therapeutic monitoring and concern about bleeding events remains an important barrier to the appropriate use of anticoagulant therapy in the Chinese population (25,26). The cost of routine dabigatran or rivaroxaban anticoagulation is too high to be affordable for ordinary patients.…”
Section: Discussionmentioning
confidence: 99%